Teaching ESL Beginners Metacognitive Writing Strategies Through Multimedia Software - Wei, J.; Chen, Julian; Adawu, A. (California Teachers of English to Speakers of Other Languages, 2014)
This case study explores how strategy-based instruction (SBI),assisted by multimedia software, can be incorporated to teachbeginning-level ESL learners metacognitive writing strategies.Two beginning-level adult learners participated in a 10-sessionSBI on planning and organizing strategies. The CognitiveAcademic Language Learning Approach (CALLA) was implementedwith the aid of graphic organizer software. Our findingsshow that technology-supported SBI has brought multiplebenefits for the learners. Comparisons of writings beforeand after SBI indicate that there is noticeable improvement inlearners’ ability to generate ideas and in logical organizationof their essays. Researchers’ observation notes and learners’reflections suggest that learners’ engagement and motivationare boosted during their prewriting activities using the graphicorganizer software. A close examination of the semantic mapsgenerated from the writing software also reveals how learnerspractice metacognitive planning and organizing strategies fortheir writing. Finally, recommendations are made for futureinstructors and researchers investigating this topic.